Pengaruh Pemulsaan Jerami Padi dan Sistem Olah Tanah Terhadap Pertumbuhan dan Hasil Tanaman Kedelai (Glycine max L. Merril) Non-Organik - Lutfy Ditya Cahyanti (Florea : Jurnal Biologi dan Pembelajarannya, 2017)
One of the factors that decrease the production of the soybean crop is the low level of soil fertility. Soil fertility can be improved with the use of mulch combined with proper tillage. This Research is needed to determine the dose and the right soil processing combined with optimal doses of straw mulch to improve the growth and yield of soybean.This research conducted wit Split Plot Design with three replication, with soil tillage as main plot and rice straw mulch as sub plot. Soil tillage arranged with 3 level, O1:  maximum soil tillageO2: minimum soil tillage and O3: without soil tillage. Rice straw mulch arranged with 4 level, M0: without rice straw mulch (control), M1: rice straw mulch 2 ton/ha, M2: rice straw mulch 4 ton/ha and M3: rice straw mulch 6 ton/ha. The results showed there were no significant interactions and influences between pemulsaaan treatment combined with tillage on the growth and yield of soybean. One of the factors that decrease the production of the soybean crop is the low level of soil fertility. Soil fertility can be improved with the use of mulch combined with proper tillage. This Research is needed to determine the dose and the right soil processing combined with optimal doses of straw mulch to improve the growth and yield of soybean.This research conducted wit Split Plot Design with three replication, with soil tillage as main plot and rice straw mulch as sub plot. Soil tillage arranged with 3 level, O1:  maximum soil tillageO2: minimum soil tillage and O3: without soil tillage. Rice straw mulch arranged with 4 level, M0: without rice straw mulch (control), M1: rice straw mulch 2 ton/ha, M2: rice straw mulch 4 ton/ha and M3: rice straw mulch 6 ton/ha. The results showed there were no significant interactions and influences between pemulsaaan treatment combined with tillage on the growth and yield of soybean.Key words: Soybean, Rice Straw Mulch dan Soil Tillage.